The Disappearing “All”: Rethinking Quantifier Float in Nigerian Languages - Aaron Ogbonnah Nwogu (Indonesian Journal of Educational Studies, 2025)
. Quantifier float, a key diagnostic for noun phrase movement in languages like English, is re-examined in Nigerian languages. Elements such as Yoruba papọ̀ and Igbo dum, translated as ‘all’, appear in fixed clause-final positions rather than varying with argument movement. Syntactic tests involving negation, aspect, and serial verb constructions show these are not stranded quantifiers from A-movement. Instead, they are base-generated adverbial quantifiers or low VP-modifiers that link anaphorically to a plural argument. Their fixed distribution and semantic restrictions suggest the quantifier-float diagnostic does not apply here, indicating possible limits to A-movement in Benue-Congo languages and calling for a more nuanced, language-specific approach to movement diagnostics.